C.45 Algorithm for Classification of Causes of Landslides - Handrianto, Yopi; Farhan, Muhammad (Sinkron : jurnal dan penelitian teknik informatika, 2019)
Abstract— Natural disasters are disasters caused by natural events and cannot be avoided including earthquakes, tsunamis, volcanic eruptions, floods, hurricanes, droughts, and landslides. One of the natural disasters that often occurs in Indonesia is a landslide disaster. One of the regencies in West Java Province that had experienced a landslide was a Purwakarta district area. Landslide is one type of mass or rock mass movement, or a mixture of both, down or out of the slope due to the disruption of the stability of the soil or rocks making up the slope. With a data mining approach that uses the decision tree method or C4.5 Algorithm, a classification model will be made where the model functions as a classification of the causes of landslides in Purwakarta district.